Exploring pronunciation teaching practice in emergency remote teaching: Lesson from Indonesian high school context - Aina Khoirida; Endang Setyaningsih; Hasan Zainnuri (Universitas Sulawesi Barat, 2021)
Regardless of its importance, pronunciation practice received a small portion in EFL teaching. This issue has attracted researchers to investigate how pronunciation practice is conducted in the EFL setting and what challenges are there. The results of the investigations have provided useful insights into what happens in the EFL classrooms. However, with the global pandemic outbreak that forced massive migration to emergency remote teaching (ERT), it remains unclear how pronunciation practice is carried out. This exploratory study attempts to shed light on the matter. It aims to portray the pronunciation practice during ERT and identify the challenges faced by the teachers. To limit the scope of the study, the researchers focused the investigation only on pronunciation accuracy. Data were collected through document analysis, non-participatory observation, questionnaire, and in-depth interview after gaining consent from two senior high schools English teachers in Indonesia. The collected data were then analyzed using the interactive model of analysis. This study reveals that during ERT, pronunciation practice received a small portion of attention, as earlier studies have found. The average time allocated is 10% of the total duration of learning. Most of the accuracy training was carried out with a similar pattern of activities, i.e., read aloud, listen-and-repeat, and teachers’ corrective feedback as the response of the student's errors. Presented in ERT, pronunciation accuracy training experienced several problems, and the most prominent is related to the internet connection. A poor internet connection can be disastrous for accuracy training as implementing synchronous learning or uploading and downloading audio/video requires a good and strong internet connection. Another problem is the lack of students’ engagement to study due to the difference in sensation and excitement with face-to-face learning. These imply that adequate preparation is needed in applying pronunciation accuracy instruction, apart from the material itself.